A taste for poison: eleven deadly molecules and the killers who used them - Bradbury, Neil (St. Martin's Press, 2022)
Insulin and Mrs. Barlow's Bathtub -- Atropine and Alexandra's Tonic -- Strychnine and the Lambeth Poisoner -- Aconite and Mrs. Singh's Curry -- Ricin and Georgi's Waterloo Sunset -- Digoxin and the Angel of Death -- Cyanide and the Professor from Pittsburgh -- Potassium and the Nightmare Nurse -- Polonium and Sasha's Indiscriminate Intestine -- Arsenic and Monsieur L'Angelier's Cocoa -- Chlorine and the Killer Nurse of Lufkin -- Epilogue: The Garden of Death.